Status Of Pretrial Institutions In Indonesian Criminal Law - Prasnada, Famda Egga; Sunardi, Sunardi; Muhibbin, Moh. (Scholar Center, 2023)
This study aims to describe the position of pretrial institutions in the study of criminal law in Indonesia and to analyze the implementation of pretrial institutions as legal remedies for suspects in obtaining justice at the level of investigation and prosecution. This is a normative legal research, which examines statutory regulations in a coherent legal system and unwritten legal values ??that live in society, which are related to the suspect's efforts to obtain justice through the Pretrial Institution. The results of the study state that pretrial is one of the new institutions introduced since the existence of Law Number 8 of 1981 concerning the Criminal Procedure Code in the midst of law enforcement life. Pretrial Institution arrangements in the Criminal Procedure Code are listed in Article 1 point 10, Chapter X Part One from Article 77 to Article 83. The position of the Judicial Institution in Indonesian positive law is part of the criminal justice system, as well as being part of law enforcement in abstracto or in concreto. In practice, pretrial is usually carried out in a rule of law country like Indonesia as long as the investigation process is carried out based on the provisions of the Criminal Procedure Code, although not all pretrial decisions are won by the suspect or the party submitting them. In the process of pretrial examination hearings, of course, the facts, both juridical and material facts, will be considered.